From Cash to Code: A Bibliometric Study on Digital Payment Systems, Electronic Money, and Fintech (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Digital payment systems have become one of the main innovations in financial transformation. Over the past few years, these systems have gained significant traction and are now at the forefront of reshaping financial landscapes globally. Currently, digital payment systems have changed global transactions by slowly replacing the transaction patterns of societies that were previously dominated by conventional transactions, offering more efficiency, security, and accessibility. This transformation is closely related to the development of fintech, which has given rise to instruments in the form of electronic money and blockchain technology. These advancements have not only changed the way payments are made but also enabled the inclusion of previously underserved populations in the financial ecosystem. This study uses a bibliometric approach to analyze scientific publications, with the main sources coming from Scopus using the keywords “digital payment systems,” “electronic money,” and “fintech.” By utilizing Biblioshiny in the VOSviewer application, this study aims to examine publication trends, contributions from various countries, institutions involved, and thematic connections between topics. In conclusion, this study contributes to expanding the understanding of the development of digital payment systems, while also presenting a global research map that can be used as a reference for academics, researchers, and policymakers involved in financial innovation.